2020
DOI: 10.1126/sciadv.aba0995
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant-free nanofiber vaccine induces in situ lung dendritic cell activation and T H 17 responses

Abstract: The current paradigm that subunit vaccines require adjuvants to optimally activate innate immunity implies that increased vaccine reactogenicity will invariably be linked to improved immunogenicity. Countering this paradigm, nanoparticulate vaccines have been reported to act as delivery systems for vaccine antigens and induce immunity without the need for exogenous adjuvants or local inflammation; however, the mechanisms underlying the immunogenicity of nanoparticle vaccines are incompletely identified. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 43 publications
(58 reference statements)
2
31
0
Order By: Relevance
“…The FSFC technology enables both structural and functional characterization of immune cells for vaccine studies, including dendritic cell antigen presentation and migration to lymph node and polarization and proliferation of effector T cells, by quantifying the expression of multiple transcriptional factors T-bet, Gata3, RORγt, Bcl6, Foxp3. Si et al designed an adjuvant-free nano vaccine that induces in situ lung dendritic cell activation and accumulation of antigen-specific Th17 T cells in lymph node and lung, with subsequent induction of a protective response (Si et al, 2020). The study by Bommireddy et al showed that a vaccine using tumor membrane vesicles (TMV), enhances the efficacy of anti-PD1 immune checkpoint treatment in inhibitor-resistant squamous cell carcinoma.…”
Section: Fsfc Contributions To Cancer Immunotherapy Researchmentioning
confidence: 99%
“…The FSFC technology enables both structural and functional characterization of immune cells for vaccine studies, including dendritic cell antigen presentation and migration to lymph node and polarization and proliferation of effector T cells, by quantifying the expression of multiple transcriptional factors T-bet, Gata3, RORγt, Bcl6, Foxp3. Si et al designed an adjuvant-free nano vaccine that induces in situ lung dendritic cell activation and accumulation of antigen-specific Th17 T cells in lymph node and lung, with subsequent induction of a protective response (Si et al, 2020). The study by Bommireddy et al showed that a vaccine using tumor membrane vesicles (TMV), enhances the efficacy of anti-PD1 immune checkpoint treatment in inhibitor-resistant squamous cell carcinoma.…”
Section: Fsfc Contributions To Cancer Immunotherapy Researchmentioning
confidence: 99%
“…47 This nanofiber vaccine can be administered intranasally to promote expansion of tissue-resident immune cells. 48…”
Section: Vaccine Adjuvants and Deliverymentioning
confidence: 99%
“…The morphology and diameter of the nanofibers were also fine-tuned to influence the controlled drug release [160]. Youhui et al [14] showed that intranasal self-assembled peptide nanofiber vaccines may be a new, needle-free, and adjuvant-free method to induce protective immunity against bacterial and fungal infections involving skin and mucosal barrier surfaces. Most recently, Gholizadeh et al [161] combined a new carbon nanofiber modified carbon electrode with a human nasal epithelial mucosa on a chip to achieve real-time quantitative monitoring of nasal administration in vitro.…”
Section: Nanofibersmentioning
confidence: 99%
“…In addition, seawater, which contains natural minerals and oligo-elements, is also used for nasal irrigation. A meta-analysis comparing hypertonic saline irrigation with isotonic saline irrigation reported that patients with sinusitis benefited more with improved symptoms from hypertonic saline irrigation than from isotonic saline irrigation, especially in the younger population [ 14 ]. Another meta-analytic study recently claimed that hypertonic saline irrigation is more effective in treating CRS; however, there was no difference in smell improvement compared to isotonic saline irrigation [ 15 ].…”
Section: Compoundsmentioning
confidence: 99%